Anisotropy in carbon fiber reinforced polymer (CFRP) and its effect on induction thermography. (October 2017) - Guo, Jianguang; Gao, Xiaorong; Toma, Ewald; Netzelmann, Udo
Abstract: Lock-in induction thermography was carried out on uniaxial, biaxial, and multi-ply woven carbon fiber reinforced polymers (CFRPs) at an induction frequency of approximately 300 kHz and at modulation frequencies of 0.4–36 Hz to detect defects in them. The measurements were performed in reflection and transmission modes. In the uniaxial material, heating occurred far away from the excitation coil. Lines of minimal heating were observed. The modulation frequency dependence of the amplitude showed an inverse proportionality, indicating volume heating. The multi-ply woven CFRP plates with impacts of 3 and 5 J showed distinct contrast because of cracked fibers. The results were compared with those obtained using optically excited thermography and X-ray tomography. Highlights: Induction thermography on uniaxial CFRP is possible. Lines of minimal heating may occur in induction thermography of CFRP. Analysis for the modulation frequency dependence of the thermal signal from CFRP verifies volume heating. Comparison of induction thermography, optically excited thermography and X-ray tomography on damaged CFRP demonstrates sensitivity for fiber breakage.